DOES IPO IMPROVE COMPANY FINANCIAL PERFORMANCE: THE CASE OF INDONESIA. - Aprilian Lahamido; Mohammad Nofal; Muslimin; Anisah (RADJA PUBLIKA, 2026)
This study aims to analyze the differences in financial performance of companies before and after an Initial Public Offering (IPO) in Indonesia. The study uses a quantitative approach with a comparative approach. The sample consists of companies that conducted an IPO on the Indonesia Stock Exchange in 2022, with an observation period of two years before the IPO (2020–2021) and two years after the IPO (2023–2024). The data used is secondary data obtained from the companies' annual financial reports. Financial performance is measured using liquidity ratios, leverage, profitability, activity, and asset growth. Analysis was conducted using nonparametric statistical tests to identify differences in financial performance before and after the IPO. The results show that an IPO causes significant changes in a company's financial performance, but the direction of these changes does not always indicate an increase. Most companies experienced a decline in profitability after the IPO, while asset growth tended to increase. These findings suggest that an IPO plays a more significant role as a means of funding and corporate growth rather than a direct determinant of improved financial performance. This study contributes to understanding the impact of an IPO on the financial performance of companies in Indonesia.